Karisma dan Otoritarianisme: Analisis Pengaruh Kepemimpinan Presiden Burkina Faso terhadap Kualitas Demokrasi Nasional - Multazam, M Billy; Abdulloh Moh Rifqi; Abdurrahman Marzuki (Kaganga:Jurnal Pendidikan Sejarah dan Riset Sosial Humaniora, 2026)
The purpose of this study is to analysis the relationship between presidential leadership in Burkina Faso and the quality of national democracy by focusing on the dynamics of charisma and authoritarianism in political leadership. Burkina Faso is situated within an unstable hybrid democratic system, marked by the popular uprising in 2014 and the military coup in 2022, reflecting fragile democratic institutions and executive dominance. The research method employed is a qualitative approach using theoretical analysis that integrates authoritarian, participatory, and laissez-faire leadership theories to assess presidential leadership characteristics and their implications for democratic practices. Data are analysis descriptively and analytically by examining political, social, and economic dynamics influencing national democratic stability. The results show that authoritarian-oriented leadership has significantly contributed to the deterioration of democratic quality in Burkina Faso. Charismatic elements of leadership are frequently utilized to strengthen regime legitimacy, while authoritarian practices, including the use of informal self-defense groups such as the Volunteers for the Defense of the Patherland (VDP), undermine democratic mechanisms. Restrictions on press freedom and pressure on the media further exacerbate democratic decline. The conclusion of this study emphasizes that improving democratic quality in Burkina Faso requires a transition toward more democratic and service-oriented leadership, the strengthening of democratic institutions, and the protection of press freedom as essential pillars of democratization. Keywords: Authoritarianism, Burkina Faso, Charisma, Democracy, Leadership.